Dehydrogenation of perhydro-N-ethylcarbazole under reduced total pressure - Kiermaier, Stephan; Lehmann, Daniel; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2021)
Liquid organic hydrogen carrier (LOHC) systems represent a promising storage option for hydrogen produced from renewable electricity by water electrolysis. Regarding the efficiency of the endothermal hydrogen release reaction, this technology greatly benefits from a direct heat integration with the waste heat of the energetic use of the released hydrogen, e. g. in a fuel cell. To enable such beneficial set-up, the reaction temperature of hydrogen release must be below the operation temperature of the applied fuel cell which calls for both low temperature dehydrogenation catalysis and high temperature fuel cell operation. This paper demonstrates that such combination may be suitable if reduced pressure dehydrogenation of perhydro-N-ethylcarbazole (H12-NEC) is combined with hydrogen electrification in a high temperature polymer electrolyte membrane fuel cell (HT-PEMFC). Dehydrogenation reactions of H12-NEC were carried out between 160 °C and 200 °C applying different hydrogen partial pressures in the dehydrogenation unit to mimic the effect of a sucking fuel cell operation mode, i.e. the reduction of hydrogen partial pressure in the dehydrogenation unit caused by the fuel cell operation. Our kinetic analysis reveals that a dehydrogenation temperature of 180 °C combined with 500 mbar hydrogen partial pressure represent, for example, a suitable parameter set for efficient hydrogen release.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Dehydrogenation; Fuel cell; Hydrogen partial pressure; LOHC; N-ethylcarbazole